PERAN INDUSTRI KERAJINAN ALAT MUSIK TRADISIONAL GAMELAN DALAM MENDUKUNG KETAHANAN EKONOMI KELUARGA (Studi di Desa Kauman, Kecamatan Karangrejo, Kabupaten Magetan Provinsi Jawa Timur) - , Muryanti, Prof. Drs. Kasto, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purposes of this study are to find out the role of gamelan traditional musical instrument industry and the percentage of contribution to the economic security of family in Kauman Village, Karangrejo Subdistrict, Magetan Regency, East Java Province. It was a descriptive study with primary data collected using questionnaires distributed to a sample of 45 gamelan craftsmen. Interviews were also done with entrepreneurs, government officials, and local community figures to explore in-depth information. Data analysis was conducted using quantitative and qualitative techniques. Results of the study show that the gamelan traditional music instrument industry in Kauman performed the roles and functions in accordance with the goal of such industry in the village. It can be seen from the fact that the craftsmen have enjoyed the strategic existence of gamelan traditional music instrument industry as an education media, welfare creation, and tourism attraction. They also realized the physiological function of gamelan traditional music instrument industry with a statistically significant effect. Several constraints faced by the gamelan musical instrument craftsmen were as follows: expensive raw materials, marketing, lack of government support, and so on. It is expected that an increasing understanding on the values of the gamelan traditional musical instrument industry in Kauman Village will enhance the spirit of progress in improving the welfare of family, thus avoiding anarchical or other negative attitudes due to the poor economic condition and famine, supporting stable and developed economic conditions, and increasing the persistence of defending the Unitary State of the Republic of Indonesia. The percentage of contribution given by the gamelan musical instrument industry to the family economic security in the village was 63%. Based on the results, it can be concluded that the existence of the gamelan musical instrument industry could boost the economic walfare of entrepreneurs and craftsmen, as well as their own families. The gamelan musical instrument industry has more existed as indicated by the increased acceptance of gamelan art in society, the increased expansion of market, and the increased economic security of family.